Analisis Penyerapan Tenaga Kerja Pada Sektor Industri - Riyadi, Muhammad (Universitas Bumigora, 2025)
The purpose of this research is to analyze the factors that influence Labor Absorption. (Studi kasus pada industri keajian emas dan mutiara Kecamatan Sekarbela, Kota Mataram). The variables that influence the absorption of labor in the gold and pearl handicraft industry in Sekarbela District, Mataram City are wages, capital, and production value. The type of research is descriptive quantitative research that uses interviews, questionnaires, and documentation to collect data on the condition of the subjects being studied. The research location is in the MSME gold and pearl craft industry along Sultan Kaharudin Street, Sekarbela District, Mataram City, for more than a month as needed. The population of this study consists of 32 owners of gold and pearl craft SMEs in the Sekarbela District. This research uses the multiple linear regression analysis method. The results of this study indicate that partially, the wage and production value variables significantly affect labor absorption. Meanwhile, the capital variable does not significantly affect labor absorption in the gold and pearl handicraft SMEs in Sekarbela District, Mataram City. Simultaneously, the wage, capital, and production value variables significantly affect labor absorption in the gold and pearl handicraft SMEs in Sekarbela District, Mataram City.